The Relationship between Early Initiation of Breastfeeding and Exclusive Breastfeeding in the Work Area of Wiyung Public Health Center, Surabaya - Nisrina, Vira Dwi; Wiyasihati, Sundari Indah; Fatmaningrum, Widati; Sulistiawati, Sulistiawati (Universitas Airlangga, 2019)
Introduction: In Indonesia, there has been a 10% increase in the span of five years for exclusive breastfeeding, however this is still far from the national target. One of the factors that can cause low rates of national exclusive breastfeeding is that not all babies have received an early initiation of breastfeeding. The purpose of this study was to determine the relationship between early initiation of breastfeeding and exclusive breastfeeding for babies aged 7-12 months in the work area of Wiyung Public Health Center, Surabaya. Methods: This study was a quantitative research with a cross-sectional approach. The study used a questionnaire as the research instrument given to 30 respondents, namely mothers who had 7-12 month old babies in the work area of Wiyung Public Health Center, Surabaya. Results: The percentage of early initiation of breastfeeding in babies aged 7-12 months was 53.33% meanwhile the percentage of exclusive was 73.33%. Using Chi Square Fisher Exact Test, it was found that there is no relationship between early initiation of breastfeeding and exclusive breastfeeding for babies aged 7-12 months in the working area of the Wiyung Public Health Center in Surabaya. (The value of p = 0.574 with a value of α = 0.05, p>α). Conclusion: The early initiation of breastfeeding is not the only factor influencing exclusive breastfeeding for babies aged 7-12 months in the work area of the Wiyung Public Health Center in Surabaya. Further research is needed on other factors that can relate to and influence exclusive breastfeeding.